2013
DOI: 10.1093/cvr/cvt187
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma brucei cathepsin-L increases arrhythmogenic sarcoplasmic reticulum-mediated calcium release in rat cardiomyocytes

Abstract: AimsAfrican trypanosomiasis, caused by Trypanosoma brucei species, leads to both neurological and cardiac dysfunction and can be fatal if untreated. While the neurological-related pathogenesis is well studied, the cardiac pathogenesis remains unknown. The current study exposed isolated ventricular cardiomyocytes and adult rat hearts to T. brucei to test whether trypanosomes can alter cardiac function independent of a systemic inflammatory/immune response.Methods and resultsUsing confocal imaging, T. brucei and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 24 publications
(33 reference statements)
1
17
0
Order By: Relevance
“…To assess this, cardiomyocytes were continuously perfused with Ang-(1-9) and a 10 mmol/l bolus of caffeine applied for 10 s after 15 min followed by 2 min of steady state measurements while cells were stimulated. The amplitude of the first Ca 2+ transient after caffeine was taken as an index of Ca 2+ influx via the L-type Ca 2+ channel 21, 22, 23. Ang-(1-9) significantly increased the L-type Ca 2+ -transient amplitude versus controls (191.8 ± 28.4 nmol/l vs. 74.6 ± 17.3 nmol/l; p < 0.05) (Figures 6F and 6G).…”
Section: Resultsmentioning
confidence: 99%
“…To assess this, cardiomyocytes were continuously perfused with Ang-(1-9) and a 10 mmol/l bolus of caffeine applied for 10 s after 15 min followed by 2 min of steady state measurements while cells were stimulated. The amplitude of the first Ca 2+ transient after caffeine was taken as an index of Ca 2+ influx via the L-type Ca 2+ channel 21, 22, 23. Ang-(1-9) significantly increased the L-type Ca 2+ -transient amplitude versus controls (191.8 ± 28.4 nmol/l vs. 74.6 ± 17.3 nmol/l; p < 0.05) (Figures 6F and 6G).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, silencing of TbCatL in BSF trypanosomes was found to have no effect on growth or morphology (Abdulla et al, 2008;Mackey et al, 2004). However, protein depletion in those studies was incomplete, and subsequently, inhibitor and RNAi studies indicated that TbCatL is indeed essential in BSF parasites (Alsford et al, 2014;Elliot et al, 2013;Steverding et al, 2012), consistent with the upregulation of endocytic and lysosomal activities associated with pathogenesis in the mammalian host (Caffrey et al, 2001;Langreth & Balber, 1975;Morgan, Allen, Jeffries, Hollinshead, & Field, 2001). trafficking.…”
Section: Discussionmentioning
confidence: 96%
“…An interesting question arising from this observation is whether CaMKII signaling might also be involved in the propagation of Chagas-associated cardiomyopathy that develops in up to 30% of patients [100], considering that an effect of T. cruzi on cardiomyocyte calcium handling is already known [7]. This thought is especially tantalizing, as it was shown that the related Trypanosoma brucei , which may also confer myocardial disease, can directly induce CaMKII-mediated proarrhythmogenic SR calcium leak in cardiomyocytes [17] and an upregulation of the chemokines CCL2 and CCL3 was found in T. cruzi -associated cardiomyopathy [53], which, we know now, is driven by CaMKII [105]. Combining Chagas disease with CaMKII conditional KO mouse models might answer this intriguing question in the future.…”
Section: Camkii In Infectious Diseasementioning
confidence: 99%